Dampak Situasi Pandemi COVID-19 terhadap Tumbuh Kembang Anak - Imas Mulyani; Dessie Wanda; Nur Agustini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the impact of the COVID-19 pandemic situation on children's growth and development. The method used is a systematic study examining 11 articles related to the effects of the COVID-19 pandemic on children's growth and development using ProQuest, CINAHL, Wiley, PubMed and ScienceDirect. The results showed that the COVID-19 pandemic had an impact on children's growth, social development of children's independence, language, fine motor skills, and gross motor skills. In conclusion, the destructive effects experienced by children while at home are stress, no opportunity to play with friends, reduced activity, weight gain, longer sleep time, increased sitting time and increased screen time. The good impact of this pandemic on individual children is that there is a positive adaptation to the process of growth and development through the maturation process and the social bonding of children and parents becomes closer. Keywords: Children, Parents, COVID-19 Pandemic, Stimulation of Growth